2012
DOI: 10.12693/aphyspola.121.941
|View full text |Cite
|
Sign up to set email alerts
|

Minor Loops in the Harrison Model

Abstract: A novel description of hysteresis phenomenon is presented. The examined description emphasizes the roles of bistability and quantum phenomena as processes responsible for hysteresis loop formation in magnetic materials. Major and symmetric minor hysteresis loops are modelled in chosen soft magnetic materials using the Harrison model. A reasonable agreement between theory and experiment is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is also important to notice the paramount role of the effective field in any attempts to develop hysteresis models compliant with thermodynamics of irreversible processes [6,7]. It has been shown that the introduction of the positive feedback mechanism expressed by the effective field either improves the overall accuracy of other hysteresis models or constitutes their foundations [28,35,44,61,70]. The effective field term in the J-A model has been extended to take into account a number of phenomena affecting the shape of hysteresis loop, e.g.…”
Section: Minor Loops Reversal Curves and Madelung Rulesmentioning
confidence: 99%
“…It is also important to notice the paramount role of the effective field in any attempts to develop hysteresis models compliant with thermodynamics of irreversible processes [6,7]. It has been shown that the introduction of the positive feedback mechanism expressed by the effective field either improves the overall accuracy of other hysteresis models or constitutes their foundations [28,35,44,61,70]. The effective field term in the J-A model has been extended to take into account a number of phenomena affecting the shape of hysteresis loop, e.g.…”
Section: Minor Loops Reversal Curves and Madelung Rulesmentioning
confidence: 99%
“…The AM curve is the basis of Jiles-Atherton model [1,2] and its modifications [3,4]. The Harrison model is also based on the AM curve [5]. The basic models of the AM curve itself, however, have not been validated experimentally for novel magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The study of phase transitions in magnetocaloric materials requires that new computational tools able to capture the effect of varying temperature on the shape of magnetization curve be developed [7][8][9][10]. In our opinion a convenient description for this purpose could be the Harrison model [11][12][13].…”
Section: Introductionmentioning
confidence: 99%